A randomized controlled trial of treatments for co‐occurring substance use disorders and post‐traumatic stress disorder. (July 2015) - McGovern, Mark P.; Lambert‐Harris, Chantal; Xie, Haiyi; Meier, Andrea; McLeman, Bethany; Saunders, Elizabeth
Abstract Background and Aims Post‐traumatic stress disorder (PTSD) is common among people with substance use disorders, and the comorbidity is associated with negative outcomes. We report on a randomized controlled trial comparing the effect of integrated cognitive–behavioral therapy (ICBT) plus standard care, individual addiction counseling plus standard care and standard care alone on substance use and PTSD symptoms. Design Three‐group, multi‐site randomized controlled trial. Setting Seven addiction treatment programs in Vermont and New Hampshire, USA. Participants/Cases Recruitment took place between December 2010 and January 2013. In this single‐blind study, 221 participants were randomized to one of three conditions: ICBT plus standard care (SC) (n = 73), individual addiction counseling (IAC) plus SC (n = 75) or SC only (n = 73). One hundred and seventy‐two patients were assessed at 6‐month follow‐up (58 ICBT; 61 IAC; 53 SC). Intervention and comparators: ICBT is a manual‐guided therapy focused on PTSD and substance use symptom reduction with three main components: patient education, mindful relaxation and flexible thinking. IAC is a manual‐guided therapy focused exclusively on substance use and recovery with modules organized in a stage‐based approach: treatment initiation, early abstinence, maintaining abstinence and recovery. SC are intensive out‐patient program services that include 9–12 hours of face‐to‐face contact per week over 2–4 days of group and individual therapies plus medication management. Measurements Primary outcomes were PTSD severity and substance use severity at 6 months. Secondary outcomes were therapy retention. Findings PTSD symptoms reduced in all conditions with no difference between them. In analyses of covariance, ICBT produced more favorable outcomes on toxicology than IAC or SC [comparison with IAC, parameter estimate: 1.10; confidence interval (CI) = 0.17–2.04; comparison with SC, parameter estimate: 1.13; CI = 0.18–2.08] and had a greater reduction in reported drug use than SC (parameter estimate: –9.92; CI = –18.14 to –1.70). ICBT patients had better therapy continuation versus IAC (P<0.001). There were no unexpected or study‐related adverse events. Conclusions Integrated cognitive behavioral therapy may improve drug‐related outcomes in post‐traumatic stress disorder sufferers with substance use disorder more than drug‐focused counseling, but probably not by reducing post‐traumatic stress disorder symptoms to a greater extent.